Administration of the fixed combination of latanoprost 0.005% and timolol 0.5% in glaucoma patients with an intraocular pressure over 30 mmHg - Yelda Buyru Özkurt (Dove Medical Press, 2009)
Yelda Buyru Özkurt, Tomris Sengor, Tufan Evciman, Melih Haboglu, Gökçen Bas, Sevda AydinFatih Sultan Mehmet Training and Research Hospital, Istanbul, TurkeyPurpose: To evaluate the intraocular pressure (IOP) reducing effect of a fixed combination of 0.005% latanoprost and 0.5% timolol in patients with an IOP of 30 mmHg or higher.Design: Prospective, randomized clinical trial.Participants: Twenty-eight patients.Methods: Patients had received no prior medical glaucoma treatment. Routine ophthalmic examinations and visual field tests were performed before and after treatment for each patient.Results: Mean IOP was 32.28 ± 0.92 mmHg before treatment. Mean IOP levels were 18.75 ± 0.68 for the first day, 17.96 ± 0.90 for the first week and 17.64 ± 0.66 for the first month after treatment.Conclusion: A fixed combination of latanoprost 0.005% and timolol 0.5% is effective in significantly reducing IOP in glaucoma patients with an IOP greater than 30 mmHg.Keywords: latanoprost, timolol, combination, glaucoma, intraocular pressure